Let's go step by step to solve the equation \( 11x - 12 + 13 = -10 \) and fill in the missing terms and descriptions.
Step 1: Combine like terms
- The left side of the equation has \( -12 \) and \( +13 \).
- Combining these gives: \[ -12 + 13 = 1 \]
- Therefore, we can rewrite the equation as: \[ 11x + 1 = -10 \]
Step 2: Subtract 1 from both sides
- Now, we will isolate the term with \( x \) by subtracting \( 1 \) from both sides: \[ 11x = -10 - 1 \]
- Simplifying the right side: \[ -10 - 1 = -11 \]
- So we have: \[ 11x = -11 \]
Step 3: Divide both sides by 11
- Next, we divide both sides by \( 11 \): \[ x = \frac{-11}{11} \]
- Simplifying the fraction gives: \[ x = -1 \]
Final results:
- Combine like terms gives us \( 11x + 1 = -10 \).
- Subtracting \( 1 \) from both sides gives us \( 11x = -11 \).
- Dividing both sides by \( 11 \) gives us \( x = -1 \).
Summary of filled terms:
- Combine like terms: \( 11x + 1 = -10 \)
- Subtract 1 from both sides: \( 11x = -11 \)
- Divide both sides by 11: \( x = -1 \)
So the final solutions to fill in the blanks are:
- First Blank: \( 11x + 1 \)
- Second Blank: \( -11 \)
- Third Blank: \( -1 \)